Is Much Psychotherapy Still Misdirected or Misapplied? - Mowrer, O. Hobart (Canadian Journal of Counselling and Psychotherapy, 2012)
In the course of the past few decades, it has become increasingly evident that psychotherapy, generally speaking, is ineffective. Yet, for want of something better, practioners and patients keep this dubious enterprise going — because psychoneurotic problems stubbornly persist, and even proliferate. It is thereforeaxiomatic that psychotherapy is being misused, in any of the several possible ways. Why is this happening? The present paper suggests three major respects in which much (perhaps most) psychotherapy and counselling is being "misdirected or misapplied." As corollaries, alternative types of remedial endeavor are suggested.